Design, development, and local production of lipid-based nutritional supplements to enhance the complementary feeding diet: A model for collaboration for a feeding trial in Bangladesh [version 1; peer review: 2 approved] - Britta Schumacher; Nuzhat Choudhury; Shahid Minhas; Georg Steiger; Saijuddin Shaikh; Abu Ahmed Shamim; Parul Christian; Rachel Fuli; Tahmeed Ahmed; Saskia de Pee; Rebecca Merrill; Nahid Hossain; et al. (Gates Open Research, 2022)
Background: Lipid-based nutrient supplements (LNS) are effective for treating childhood wasting and for preventing stunting, wasting, and anemia, but large-scale production and programmatic use are a barrier. Locally-developed and produced LNS may be more affordable and reduce logistical procurement and importation hurdles, while promoting private sector engagement and partnership. Methods: In northwestern Bangladesh, we conducted a community-based trial of complementary food supplementation to test its efficacy to reduce childhood stunting. Two locally-developed, small-quantity LNS (20g/day, rice-lentil and chick-pea based) were designed, developed first at small scale in the ‘kitchen’ laboratory under controlled conditions, followed by taking them to a local food manufacturer for larger production for the study. We describe here the partnership, required expertise and capacity, experiences, and lessons learned that made this uniquely complex undertaking possible Results: Key steps in the journey included addressing the dynamics of clear communication between partners, executing on carefully assigned tasks and roles, correcting course when needed, and maintaining timeliness and roadmaps. Knowledge of food science and technology was key in solving many food-production challenges that were encountered in taking the laboratory recipe to the factory. Factory production was established and had to meet quality and hygiene criteria set for young children. Conclusions: We provide documentation of this experience as a model to describe the various steps and considerations and what is entailed in local LNS production. We highlight the importance of a well-conceived collaboration with clear roles that created a ‘win-win’ situation for all partners for achieving common goals, establishing improved technology at the factory, and building new capacity to produce such products for children in a low resource setting. Key words: micronutrient, lipid-based nutrient supplements, maternal and child, malnutrition, multiagency collaboration